Luxury brand at the cusp of lipstick effects: Turning brand selfies into luxury brand curruncy to thrive via richcession - Raza, M.; Khalid, R.; Loureiro, S. M. C.; Han, H. (Journal of Retailing and Consumer Services, 2024)
A fear of a richcession is on the horizon. The luxury industry must rekindle customer desires and promote brand selfies in order to survive. The narcissist and materialist affluent people upload their selfies along with luxury brand signatures, and this triggers the self-inferential process in the fellow affluent and shapes their luxury preferences. This study investigates this phenomenon, the lipstick effect, and its connection with richcession. A niche group of ultra-rich affluent people was chosen based on their spending patterns, their access to famous personalities, their choice of expensive places, their usage of luxury products, and their postings of selfies with luxury signatures. The study developed a measurement scale via a three-step survey-based approach by analyzing 468 questionnaires. The confirmatory factor analysis (CFA) proposes 27 items of a new scale. The structural analysis was then conducted in order to ensure the scale validity and stability by employing a new dataset of 356 questionnaires. We demonstrated how luxury brand selfies influence luxury signature, and how this in turn affects luxury brand currency and preference.